Fractal image compression. Issue 6 (13th November 2013) - MARTIN, C. E.; CURTIS, S. A.
Abstract: This paper describes some experiences of using fractal image compression as the subject of an assignment for a functional programming course using Haskell. The students were fascinated by the reproduction of images from their encodings and engaged well with the exercise which involved only elementary functional programming techniques.